2009
DOI: 10.12942/lrsp-2009-3
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Holes

Abstract: Coronal holes are the darkest and least active regions of the Sun, as observed both on the solar disk and above the solar limb. Coronal holes are associated with rapidly expanding open magnetic fields and the acceleration of the high-speed solar wind. This paper reviews measurements of the plasma properties in coronal holes and how these measurements are used to reveal details about the physical processes that heat the solar corona and accelerate the solar wind. It is still unknown to what extent the solar win… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
318
1
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(336 citation statements)
references
References 364 publications
10
318
1
7
Order By: Relevance
“…This was suggested as a formation mechanism for large, Type I solar spicules (see also de Pontieu, 1999;Kudoh and Shibata, 1999;Matsumoto and Shibata, 2010). Cranmer and Woolsey (2015) recently extended this idea to smaller-scale turbulent Alfvénic motions in CH network regions, and found that nonlinear mode conversion into chromospheric shocks may provide intermittent upflows of the right order of magnitude. Such a model produces vertical excursions in the height of the transition region of order 1 to 6 Mm over timescales of 20 to 60 s, which gives rise to apparent jet-like velocities of 50 to 200 km s −1 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This was suggested as a formation mechanism for large, Type I solar spicules (see also de Pontieu, 1999;Kudoh and Shibata, 1999;Matsumoto and Shibata, 2010). Cranmer and Woolsey (2015) recently extended this idea to smaller-scale turbulent Alfvénic motions in CH network regions, and found that nonlinear mode conversion into chromospheric shocks may provide intermittent upflows of the right order of magnitude. Such a model produces vertical excursions in the height of the transition region of order 1 to 6 Mm over timescales of 20 to 60 s, which gives rise to apparent jet-like velocities of 50 to 200 km s −1 .…”
Section: Resultsmentioning
confidence: 93%
“…Numerous investigations are being carried out to understand where the solar wind originates and how it is accelerated (for recent reviews see Cranmer (2009) and Hansteen and Velli (2012)). Dark regions in coronal images indicate coronal holes (CHs), which are the commonly accepted large-scale source regions of high-speed solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field of CHs is mainly open, i.e., organized in magnetic For techniques used to analyze observations of CHs, it makes a difference whether the holes are observed on the disk or above the solar limb. Discussing the corresponding challenges and issues, however, lies outside the scope of this work and we refer to the review by Cranmer (2009). Here, we focus on the magnetic field structure in CHs.…”
Section: Coronal Holesmentioning
confidence: 99%
“…Magnetohydrodynamic (MHD) waves are important candidates for the heating of the solar corona and the acceleration of the fast solar wind (Cranmer 2009;Ofman 2010). Recently, McIntosh et al (2011a) reported the ubiquitous presence of outwardpropagating transverse oscillations with amplitudes of nearly 20 km s −1 and periods between 100 s and 500 s throughout the quiescent atmosphere, which according to these authors are sufficiently energetic to accelerate the fast solar wind and heat the quiet corona.…”
Section: Introductionmentioning
confidence: 99%